Nutrient deficiency and effects of various nutrition technologies on crop health - Rácz, Dalma; Radócz, László (Acta Agraria Debreceniensis, 2019)
The impacts of climate change on crop production are increasingly noticeable. Extreme weather conditions – such as devastating droughts, which occur more often – have serious effects on crop conditions, thus damaging their defence ability against pathogens and pests. Therefore, in order to achieve high-quality and high yielding crops, it is urgent to elaborate new technologies that improve general condition of crops and prevent development of nutrient diseases. Those crops which suffer from the lack of certain nutrients are more sensitive and their tolerance against diseases are decreased. Nitrogen – as the most influencing macronutrient in yield – is also essential in maintaining crop health. Nevertheless, due to the complicated processes in soil (such as leaching, denitrification), the utilization of nitrogen is not nearly complete, therefore nitrogen stabilizers may be needed to maximize this factor. The use of these stabilizers can be promising where plants with high nitrogen content are grown, although further experiments are needed in which impacts of nitrogen stabilizers on crop protection aspects are examined as well, since there is a close correlation between exaggerated nitrogen fertilizing and sensitivity to pests. During my research I am going to examine the combined effect of foliar fertilizer and nitrogen stabilizer on crop health. Furthermore, my goal is to find clear correlation between pathogens and the different technological variants of nutrition.